2022
DOI: 10.1007/s10198-021-01427-5
|View full text |Cite
|
Sign up to set email alerts
|

Value drivers of development stage biopharma companies

Abstract: Objective Scholars previously estimated research and development (R&D) costs of the internal drug development process. However, little is known about the costs and value arising from externally acquired therapeutics. This study identifies and estimates the magnitude of factors associated with Biopharma acquisition value. Methods SDC Thomson Reuter and S&P Capital IQ were screened for majority acquisitions of US and EU Biopharma companies developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, scientists leverage new technologies, including next-generation sequencing, high throughput screening, or machine learning, to quickly test hypotheses and identify optimal patient populations (and indications) for a drug [ 31 , 32 ]. Discovering platform technologies, such as targeted therapies or immuno-therapies, which can be used across multiple diseases, are especially desired and valued by investors [ 1 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, scientists leverage new technologies, including next-generation sequencing, high throughput screening, or machine learning, to quickly test hypotheses and identify optimal patient populations (and indications) for a drug [ 31 , 32 ]. Discovering platform technologies, such as targeted therapies or immuno-therapies, which can be used across multiple diseases, are especially desired and valued by investors [ 1 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multi-indication drugs offer dynamic efficiency gains for patients and manufacturers as lengthy and costly research and pre-clinical testing efforts only occur once per drug. Expanding drugs to new indications increases revenues, profits, returns, and valuations for manufacturers [ 4 , 5 ]. However, pricing and reimbursement mechanisms have not evolved at the same pace as pharmaceutical development, intensifying concerns about the affordability of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this observation could suggest that a large part of indication development is random, additional variables may be necessary to fully explain companies’ decision making in pharmaceutical development. For instance, variables characterizing an indication’s peak sales and competitive environment, the pharmaceutical company’s portfolio size, R&D partnerships of certain indications, licensing agreements, mergers and acquisitions, and underlying market conditions may influence economic decision of pharmaceutical companies throughout the drug development process [ 10 , 11 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pharmaceutical companies are incentivized to pursue research and development (R&D) in diseases with a high unmet therapeutic need with expedited clinical development and regulatory approval timelines [ 9 ]. Michaeli et al previously demonstrated this strategy yields high company valuations and excess financial returns for Bioentrepreneurs and Investors [ 10 , 11 ]. Arguably more substantial than R&D incentives could be the monetary incentive created by uniform pricing of multi-indication drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in this study, we aim to identify key value drivers of Biopharma ventures based on a cross-sectional sample of 311 Biopharma acquisitions. While it is established that Biopharma firm value is mainly dependent on the lead drug's development stage [5][6][7][8][9], we also evaluate the association of firm valuation with the lead drug's FDA orphan designation status, number of indications, molecule type, and disease area.…”
Section: Introductionmentioning
confidence: 99%